The Influence of Work Morale and Motivation on the Organizational Citizenship Behavior of Civil Servants UPT Puskesmas Gang Sehat in Pontianak City - Rizky Rahmi Lestari; Irfan Mahdi (Proceedings Series on Social Sciences & Humanities, 2024)
This research aims to investigate the influence of Work Morale and Motivation on the Organizational Citizenship Behavior of Civil Servants at the UPT Puskesmas Gang Sehat in Pontianak City. The research employs an associative research method. The population under study comprises Civil Servants working at UPT Puskesmas Gang Sehat, with a total sample size of 40 individuals. The data analysis techniques used include multiple linear regression analysis, simple correlation coefficient (R), coefficient of determination (R2), simultaneous influence test (F-test), and partial influence test (t-test). The research results indicate that the multiple linear regression equation is as follows: Y = 4.865 + 0.459X1 + 0.362X2. The results of the correlation coefficient (R) values for Work Morale are 0.668, these values indicate that the relationship between the variable Work Morale (X1) and Motivation (X2) with the variable Organizational Citizenship Behavior (Y) is significant. The coefficient of determination (R2) has a value of 0.446, indicating that 44.6% of Organizational Citizenship Behavior can be explained by Work Morale and Motivation, while the remaining 55.4% is influenced by unexamined variables in this study. The F-test results indicate a significant simultaneous influence of Work Morale and Motivation on Organizational Citizenship Behavior. The t-test results show a significant partial influence of Work Morale on Organizational Citizenship Behavior and a significant partial influence of Motivation on Organizational Citizenship Behavior.